Mengkoordinir Ragam Format Acara Dakwah - Efendi, Erwan; Salim, Muhammad; Rosadi, Imron (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This research was structured to find out about Coordinating the Formats of Da'wah Events, the results of this research are organizing, controlling, supervising the effective and efficient arrangement of da'wah programs, so that in carrying out a da'wah program it can be well controlled and acceptable to mad'u. As we know, at this point, many people are not interested in a da'wah program due to the lack of ways to coordinate various formats of da'wah events so that mad'u are not interested in the da'wah program. In coordinating the various formats of da'wah events, of course, they have their own goals, therefore we must understand their goals and functions.